Notes on the genus Kosmiomiris Kirkaldy (Hemiptera: Miridae: Hyalopeplini) with description of a new species - Kim, Junggon; Damken, Claas; Sah, Hanyrol H. Ahmad; Jung, Sunghoon (Zootaxa, 2019)
A new species of the hyalopepline genus Kosmiomiris is described, Kosmiomiris carvalhoi Kim & Jung sp. nov. Morphological information including diagnoses, descriptions of new species, and re-description of K. rubroornatus and biological notes are presented with photographs. Female genitalia of two species in this genus is described for the first time. A key to the Kosmiomiris species is also provided.